Protocol of the TREASURE study: Thoracic RadiothErapy with Atezolizumab in Small cell lUng canceR Extensive disease – a randomized, open-label, multicenter phase II trial - Farastuk Bozorgmehr; Petros Christopoulos; Inn Chung; Jelena Cvetkovic; Manuel Feißt; Johannes Krisam; Marc A. Schneider; Claus Peter Heußel; Michael Kreuter; Daniel W. Müller; Michael Thomas; Stefan Rieken (BMC Cancer, 2022)
Abstract Background Recently, the combination of the programmed death-ligand 1 (PD-L1) inhibitor atezolizumab with first-line chemotherapy has demonstrated to improve outcome for patients with advanced small cell lung cancer (SCLC), leading to approval of this regimen. At the same time, accumulating (pre-)clinical data suggest synergisms of radiotherapy and immunotherapy via the radiation-mediated induction of anti-tumor immunogenicity. Combining the recent findings, the TREASURE trial aims at further enhancing response to upfront chemo-immunotherapy by the addition of thoracic radiotherapy (TRT). Methods/design The TREASURE trial is a randomized, multicenter, phase II clinical trial ( ClinicalTrials.gov identifier, NCT04462276). One hundred four patients suffering from extensive disease (ED) SCLC, with any response to the standard of care induction chemo-immunotherapy will be randomized to receive atezolizumab maintenance therapy with or without TRT. The primary endpoint of this study is overall survival (OS). Secondary endpoints include further measures of efficacy, safety, and the collection of biomarker samples. A safety interim analysis will take place after n = 23 patients receiving TRT have been observed for three months after the end of TRT. Discussion This trial will investigate whether treatment efficacy can be improved by adding TRT to atezolizumab maintenance therapy in ED SCLC patients with any response after chemo-immunotherapy. Safety and feasibility of such a regimen will be evaluated, and biomaterials for a translational research project will be collected. Together, the results of this trial will deepen our comprehension of how checkpoint inhibition and radiotherapy interact and contribute to the evolving landscape of SCLC therapy. Trial registration Clinicaltrials.gov identifier: NCT04462276 (Date of initial registration: 8th July 2020), https://clinicaltrials.gov/ct2/show/NCT04462276 Eudra-CT Number: 2019-003916-29 (Date of initial registration: 30th March 2020), https://www.clinicaltrialsregister.eu/ctr-search/trial/2019-003916-29/DE